2010
DOI: 10.2147/vhrm.s9252
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and effectiveness of a disease and care management model in the primary health care system for patients with heart failure and diabetes (Project Leonardo)

Abstract: PurposeProject Leonardo represented a feasibility study to evaluate the impact of a disease and care management (D&CM) model and of the introduction of “care manager” nurses, trained in this specialized role, into the primary health care system.Patients and methodsThirty care managers were placed into the offices of 83 general practitioners and family physicians in the Apulia Region of Italy with the purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
258
0
11

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 305 publications
(277 citation statements)
references
References 17 publications
8
258
0
11
Order By: Relevance
“…The control group (Group B) comprised 46 patients (44 girls and 2 boys), with a mean age at the time of the surgery of 15.2 ± 1.6 years (ages [11][12][13][14][15][16][17][18][19]) and the mean magnitude of the Cobb angle before surgery was 68° ± 14° (46°-101°). In this group, the most prevalent curves were double primary curves (41% of patients) and thoracic primary curves (41% of patients).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The control group (Group B) comprised 46 patients (44 girls and 2 boys), with a mean age at the time of the surgery of 15.2 ± 1.6 years (ages [11][12][13][14][15][16][17][18][19]) and the mean magnitude of the Cobb angle before surgery was 68° ± 14° (46°-101°). In this group, the most prevalent curves were double primary curves (41% of patients) and thoracic primary curves (41% of patients).…”
Section: Resultsmentioning
confidence: 99%
“…However the authors want emphasize the importance of cooperation between the entire team of specialists in the treatment of idiopathic scoliosis, in particular physiotherapists and orthopedists, at such a critical moment when the decision of conducting a surgery must be made. Ciccone et al [18] report that a strong cooperative team is significant during the treatment. In this study (Project Leonardo) physicians, care managers and patients demonstrated unanimous agreement concerning the positive impact on patient health and self-management.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Daily cooking is also essential for health. Care managers should manage both the residents' nutrition for health and cooking environment, with cooperation of other health personnel [5].…”
Section: Case 2: a 78 Year Old Woman With Suspected Mild Dementiamentioning
confidence: 99%
“…For example, Ciccone et al [25] have presented Project Leonardo which examined the Chronic Care Model developed by Wagner et al [26] based on partnership between the patient and health professionals. This model offers the opportunity to empower patients to become more active in managing their health.…”
Section: Ratio (Svr)mentioning
confidence: 99%